Long‐term anticholinergic use and the aging brain. Issue 4 (26th November 2012) - Cai, Xueya; Campbell, Noll; Khan, Babar; Callahan, Christopher; Boustani, Malaz
Abstract: Background: Older Americans are facing an epidemic of chronic diseases and are thus exposed to anticholinergics (ACs) that might negatively affect their risk of developing mild cognitive impairment (MCI) or dementia. Objective: To investigate the association between impairment in cognitive function and previous AC exposure. Design: A retrospective cohort study. Setting: Primary care clinics in Indianapolis, Indiana. Participants: A total of 3690 older adults who have undergone cognitive assessment and had a 1‐year medication‐dispensing record. Outcome: Cognitive function was measured in two sequential steps: a two‐step screening process followed by a formal diagnostic process for participants with positive screening results. Exposure: Three patterns of AC exposure were defined by the duration of AC exposure, the number of AC medications dispensed at the same time, and the severity of AC effects as determined by the Anticholinergic Cognitive Burden list. Results: Compared with older adults with no AC exposure and after adjusting for age, race, gender, and underlying comorbidity, the odds ratio for having a diagnosis of MCI was 2.73 (95% confidence interval, 1.27–5.87) among older adults who were exposed to at least three possible ACs for at least 90 days; the odds ratio for having dementia was 0.43 (95% confidence interval, 0.10–1.81). Conclusion: Exposure to medications with severe AC cognitive burden may be a risk factor for developing MCI.